Sengketa Jual Beli Tanah Persil Atau Belum Bersertifikat (Studi Kasus Putusan Di Pn Surakarta) - Ramadhan, Rizky, Darsono, S.H, M.H (2016)
This study aims to analyze the problems of the settlement of land certificates certified and consideration of the judge in taking the decision to purchase land disputes that have not been certified. This study uses normative legal approach. Data collection techniques in this research is the study of literature. Data analysis techniques in this study using qualitative data analysis. Methods of ualitative data analysis is done by analyzing the court decision relating to dispute settlement land sales that have not been certified. The results showed that the problems of the settlement of land certificates certified are: 1) the occurrence of buying and selling physical mastery has been dominated by the plaintiff, 2) the claimant is now in dire need of juridical ownership and 3) The Defendants objected. Consideration of judges in taking the decision to purchase land disputes that have not been certified are: 1) The defendant has been summoned by a legitimate, 2) Decision dated March 6, 1971 Number: 209 K / Sip / 1971 has been decided that a change is not contrary to the demands of a principles of civil law, 3) the District Court took a stance of its own, and 4) the old owner has died while heirs had not known where he lived with certainty.